Modelo de ising de spins mistos em uma rede triangular com anisotropias aleatórias - Santana, Elpidio Sousa (2018)
The objective of this dissertation is to map the lines of phase transitions in a ferrimagnetic system. For this reason, we used the Monte Carlo simulations in the Ising model of mixed spins in a triangular lattice under the influence of random anisotropies. This lattice is divided into three other interpenetrating sublattices, with the σ = 1/2 spins occupying the sublattices A and B, and the spins S = 1 forming the subnet C. The network has ferromagnetic interaction (J < 0) between its spins and we have a random distribution of the anisotropy DC k in the sublattice C. To determine the magnetic properties of the system, we calculate some thermodynamic properties such as staggered magnetization, susceptibility, energy, specific heat, for various system sizes. We construct the phase diagram of the model in the critical temperature plane Tc versus anisotropy D, which presents lines of first and second order phase transitions for different anisotropy distributions.